Environmentally friendly glass materials
An environmentally friendly glass composition with SiO2, ZnO, and alkali metal oxides addresses the issues of cadmium toxicity and stability in selenocadmium glass, offering UV/visible light cutoff and high near-infrared transmittance for smart devices.
Patent Information
- Application Number
- JP2022581660
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-30
- Filing Date
- 2021-05-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-05-12
AI Technical Summary
Conventional selenocadmium glass used for near-infrared detection in smart devices is environmentally harmful due to cadmium content and has low chemical stability, making it unsuitable for harsh environments.
A glass composition comprising SiO2, ZnO, alkali metal oxides, and S, with specific ratios, achieving a cutoff wavelength of 550 nm or more and high near-infrared transmittance without cadmium, along with improved chemical stability and thermal properties.
The environmentally friendly glass material provides effective ultraviolet/visible light cutoff and high near-infrared transmittance, meeting environmental standards and ensuring stability for smart devices.
Smart Images

Figure 0007599508000004 
Figure 0007599508000001 
Figure 0007599508000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a glass material, and more particularly to an environmentally friendly glass material that has ultraviolet and visible light blocking properties and high near-infrared transmittance. [Background technology]
[0002] In recent years, with the development of the optoelectronics industry, the use of near-infrared wavelength band detection from 800nm to 2000nm has become increasingly important, especially in smart devices. Near-infrared lasers are urgently needed for real-time sensing of the surrounding environment to determine the operation and movement of smart devices. Its implementation is based on the fact that optical systems need to eliminate ultraviolet and visible light bands that interfere with the near-infrared operating band, and therefore require higher transmittance in the near-infrared band.
[0003] Conventional selenocadmium glass can cut off ultraviolet and visible light bands and has higher near-infrared transmittance. Its disadvantage is that it contains a lot of cadmium (Cd), which does not meet current environmental standards and causes great harm to the environment and human body during its manufacturing, use and disposal. In addition, selenocadmium glass has low chemical stability and is not suitable for smart devices that need to withstand harsh environments. Summary of the Invention [Problem to be solved by the invention]
[0004] The technical problem to be solved by the present invention is to provide an environmentally friendly glass material that has ultraviolet and visible light blocking properties and high near-infrared transmittance. [Means for solving the problem]
[0005] The technical solutions adopted in the present invention to solve the technical problems are as follows: (1) SiO 2An environmentally friendly glass material which contains components such as ZnO, an alkali metal oxide and S, but does not contain Cd, and which has a cutoff wavelength of 550 nm or more, a transmittance of 75% or more at 800 to 850 nm, a transmittance of 80% or more at 850 to 900 nm, a transmittance of 83% or more at 900 to 1000 nm, and a transmittance of 85% or more at 1000 to 2000 nm when the thickness of the environmentally friendly glass material is 3 mm. (2) The environmentally friendly glass material according to (1), wherein when the thickness of the environmentally friendly glass material is 3 mm, the cutoff wavelength is 600 nm or more, preferably 650 nm or more, more preferably 680 nm or more, and even more preferably 700 nm or more. (3) The environmentally friendly glass material according to (1), which has a transmittance of 77% or more at 800 to 850 nm, preferably 80% or more at 800 to 850 nm, when the environmentally friendly glass material has a thickness of 3 mm. (4) The environmentally friendly glass material according to (1), which has a transmittance of 82% or more at 850 to 900 nm, preferably 83% or more at 850 to 900 nm, when the environmentally friendly glass material has a thickness of 3 mm. (5) The environmentally friendly glass material according to (1), which has a transmittance of 84% or more at 900 to 1000 nm, preferably 85% or more at 900 to 1000 nm, when the environmentally friendly glass material has a thickness of 3 mm. (6) The environmentally friendly glass material according to (1), which has a transmittance of 86% or more at 1000 to 2000 nm, preferably 87% or more at 1000 to 2000 nm, when the environmentally friendly glass material has a thickness of 3 mm. (7) Its components expressed in weight percent: SiO 2 35-80%; ZnO 5-35%; Na 2 O: 5-25%; K: 2 The environmentally friendly glass material according to (1), comprising 1 to 10% O; 0.2 to 8% S; and 0.5 to 10% Sb+Ag+Ce+Sn+Te+V+Fe. (8) Its components expressed in weight percent: Li 2 O 0-5%; and / or B 2 O 30 to 10%; and / or Al 2 O 3 and / or 0 to 5% MgO; and / or 0 to 5% CaO; and / or 0 to 10% SrO; and / or 0 to 10% BaO; and / or 0 to 5% Se; and / or 0 to 5% F. (9) Its components expressed in weight percent: SiO 2 35-80%; ZnO 5-35%; Na 2 O: 5-25%; K: 2 O 1-10%; Li 2 O 0-5%; S 0.2-8%; Sb+Ag+Ce+Sn+Te+V+Fe 0.5-10%; B 2 O 3 0-10%; Al 2 O 3 An environmentally friendly glass material containing 0%-5%; MgO 0-5%; CaO 0-5%; SrO 0-10%; BaO 0-10%; Se 0-5%; and F 0-5%, and does not contain Cd. (10) Its components, expressed in weight percent, are: SiO 2 and / or ZnO 7 to 30%; and / or Na 2 O 7-22%; and / or K 2 O 2-8%; and / or Li 2 O 0-3%; and / or S 0.5-7%; and / or Sb+Ag+Ce+Sn+Te+V+Fe 0.8-9%; and / or B 2 O 3 0 to 5%; and / or Al 2 O 3 and / or 0 to 3% of MgO; and / or 0 to 3% of CaO; and / or 0 to 5% of SrO; and / or 0 to 5% of BaO; and / or 0 to 4% of Se; and / or 0 to 3% of F. (11) Its components, expressed in weight percent, are: SiO 2 42 to 73%; and / or ZnO 9 to 25%; and / or Na 2 O 8-19%; and / or K 2O 3-7%; and / or S 1-6%; and / or Sb+Ag+Ce+Sn+Te+V+Fe 0.9-8%; and / or Se 0-3%; and / or Li 2 O 0-2%; and / or B 2 O 3 0 to 3%; and / or Al 2 O 3 and / or 0 to 2% MgO; and / or 0 to 2% CaO; and / or 0 to 2% SrO; and / or 0 to 2% BaO; and / or 0 to 1% F. (12) Its components expressed in weight percent are: CuO + TiO 2 +P 2 O 5 0 to 0.5%; preferably CuO + TiO 2 +P 2 O 5 0.0001 to 0.5%; more preferably CuO + TiO 2 +P 2 O 5 0.0001 to 0.4%; more preferably CuO + TiO 2 +P 2 O 5 The environmentally friendly glass material according to any one of (1) to (9), containing 0.0001 to 0.3% of (13) The components are expressed in weight percent, B 2 O 3 / SiO 2 is 0.23 or less, preferably B 2 O 3 / SiO 2 is 0.15 or less, more preferably B 2 O 3 / SiO 2 The environmentally friendly glass material according to any one of (1) to (9), wherein is 0.1 or less. (14) The composition is expressed in weight percent and is ZnO / SiO 2 is 0.07 to 0.95, preferably ZnO / SiO 2 is 0.10 to 0.75, more preferably ZnO / SiO 2 The environmentally friendly glass material according to any one of (1) to (9), wherein the value is 0.15 to 0.60. (15) An environmentally friendly glass material according to any one of (1) to (9), wherein the components are expressed in weight percent and the Se / S ratio is 1.5 or less, preferably 1.3 or less, more preferably 1.0 or less, and even more preferably 0.5 or less. (16) The environmentally friendly glass material according to any one of (1) to (9), wherein the components are expressed in weight %, and (Sb+Ag+Ce+Sn+Te+V+Fe) / (Se+S) is 0.1 to 25.0, preferably (Sb+Ag+Ce+Sn+Te+V+Fe) / (S+Se) is 0.2 to 15.0, more preferably (Sb+Ag+Ce+Sn+Te+V+Fe) / (S+Se) is 0.5 to 8.0, and even more preferably (Sb+Ag+Ce+Sn+Te+V+Fe) / (S+Se) is 1.0 to 5.0. (17) The environmentally friendly glass material according to any one of (1) to (9), wherein the components are expressed in weight percent, and (Ag+Ce+Sn+Te+V+Fe) / Sb is 3.0 or less, preferably (Ag+Ce+Sn+Te+V+Fe) / Sb is 2.0 or less, more preferably (Ag+Ce+Sn+Te+V+Fe) / Sb is 1.0 or less, and even more preferably (Ag+Ce+Sn+Te+V+Fe) / Sb is 0.8 or less. (18) Its composition is expressed in weight percent and Li 2 O+Na 2 O+K 2 O is 8 to 35%, preferably Li 2 O+Na 2 O+K 2 O is 9 to 30%, and more preferably Li 2 O+Na 2 O+K 2 The environmentally friendly glass material according to any one of (1) to (9), wherein O is 10 to 22%. (19) B 2 O 3 Does not contain Li 2 An environmentally friendly glass material according to any one of (1) to (9), which is free of O; and / or free of Sn; and / or free of Te. (20) The environmentally friendly glass material according to (9), wherein when the thickness of the environmentally friendly glass material is 3 mm, the cutoff wavelength is 550 nm or more, preferably 600 nm or more, more preferably 650 nm or more, even more preferably 680 nm or more, and still more preferably 700 nm or more. (21) When the thickness of the environmentally friendly glass material is 3 mm, the transmittance at 800 to 850 nm is 75% or more, preferably the transmittance at 800 to 850 nm is 77% or more, and more preferably the transmittance at 800 to 850 nm is 80% or more; and / or when the thickness of the environmentally friendly glass material is 3 mm, the transmittance at 850 to 900 nm is 80% or more, preferably the transmittance at 850 to 900 nm is 82% or more, and more preferably the transmittance at 850 to 900 nm is 83% or more; and / or and / or the environmentally friendly glass material according to (9), wherein when the thickness of the environmentally friendly glass material is 3 mm, the transmittance from 900 to 1000 nm is 83% or more, preferably the transmittance from 900 to 1000 nm is 84% or more, and more preferably the transmittance from 900 to 1000 nm is 85% or more, when the thickness of the environmentally friendly glass material is 3 mm, the transmittance from 1000 to 2000 nm is 85% or more, preferably the transmittance from 1000 to 2000 nm is 86% or more, and more preferably the transmittance from 1000 to 2000 nm is 87% or more. (22) The environmentally friendly glass material has an acid resistance stability of Class 3 or higher, preferably Class 2 or higher, and more preferably Class 1; and / or a water resistance stability of Class 3 or higher, preferably Class 2 or higher, and more preferably Class 1; and / or a thermal expansion coefficient of 80×10 -7 / K or more, preferably 85×10 -7 / K or more, preferably 90×10 -7 / K or more, and more preferably 95×10 -7 / K or more. (23) A glass preform using the environmentally friendly glass material according to any one of (1) to (22). (24) A glass member using the environmentally friendly glass material according to any one of (1) to (22) or the glass preform according to (23). (25) A device comprising the environmentally friendly glass material according to any one of (1) to (22) and / or the glass member according to (24). (26) A method for producing an environmentally friendly glass material according to any one of (1) to (22), comprising the following steps: 1) Mix all the raw materials according to the component ratio of the environmentally friendly glass material, put the homogeneously mixed raw materials into a melting furnace, and melt them at 1300~1500℃ to form molten glass; 2) Stirring and homogenizing the molten glass; 3) Pouring or leaking the molten glass into a mold to form it; 4) The glass formed in step 3) is held at 470 to 600°C for 10 to 60 hours to develop color, or the glass formed in step 3) is further processed into a glass preform or a glass member, and then held at 470 to 600°C for 10 to 60 hours to develop color. (27) A method for producing an environmentally friendly glass material according to (26), wherein a compound salt, and / or a hydroxide, and / or an oxide, and / or a sulfide, and / or a selenide, and / or a fluoride, and / or an element is used as a raw material for the environmentally friendly glass material. Effect of the Invention
[0006] The beneficial effect of the present invention is that, through rational component design, the glass material of the present invention achieves ultraviolet and visible light blocking and high near-infrared transmittance while being environmentally friendly. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a curve graph showing the spectral transmittance of an environmentally friendly glass material according to a second embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, the embodiments of the present invention will be described in detail, but the present invention is not limited to the embodiments described below, and can be modified as appropriate within the scope of the object of the present invention. Furthermore, repeated explanations will be omitted as appropriate, but this does not limit the gist of the present invention. Hereinafter, the environmentally friendly glass material of the present invention may be referred to as glass.
[0009] [Environmentally friendly glass materials] The ranges of the components (constituent elements) of the environmentally friendly glass material of the present invention will be described below. In this specification, unless otherwise specified, the content of each component and the total content are expressed in weight % (wt%).
[0010] Numerical ranges set forth in this specification include upper and lower limits unless otherwise stated, and the terms "greater than or equal to" and "less than or equal to" include the endpoints, and all integers and fractions within the range, but are not limited to the specific values set forth when a range is limited. References to "and / or" in this specification are inclusive, e.g., "A and / or B" means A only, B only, or both A and B.
[0011] <Required and optional ingredients> SiO 2 is one of the main components of glass. In the glass of the present invention, an appropriate amount of SiO 2 stabilizes the color and enables the glass to achieve the desired cutoff performance. On the other hand, a suitable amount of SiO 2 This allows the chemical stability of the glass to be improved. 2 If the content of SiO is less than 35%, the cut-off performance of the glass does not meet the design requirements, and the chemical stability of the glass is rapidly reduced. 2 The lower limit of the SiO content is 35%, preferably 40%, and more preferably 42%. 2If the content of SiO in the present invention exceeds 80%, the melting temperature of the glass rises sharply, the volatilization of coloring substances increases, and the cut-off performance of the glass decreases. At the same time, the high-temperature viscosity of the glass rises sharply, and the number of bubbles and inclusions in the product increases sharply. Therefore, the SiO 2 The upper limit of the content is 80%, preferably 75%, and more preferably 73%.
[0012] B in the glass of the present invention 2 O 3 improves the melting performance of glass and enhances the essential quality and chemical stability of glass. However, the inventors have found through their research that B in glass 2 O 3 It was found that B causes changes in the glass structure, increases the threshold for binding of coloring substances, and reduces the cut-off ability of the glass. Therefore, if the cut-off ability of the glass meets the requirements, it is necessary to add B to improve the melting performance and chemical stability of the glass. 2 O 3 In one implementation, B may include 10% or less, preferably 5% or less, and more preferably 3% or less. 2 O 3 It is more preferable that it does not contain
[0013] The present invention, through extensive experimental studies, has demonstrated that, in several implementations, 2 O 3 / SiO 2 It has been found that by making the B content 0.23 or less, the water resistance stability of the glass can be improved while optimizing the cutoff performance of the glass. 2 O 3 / SiO 2 is 0.15 or less, more preferably B 2 O 3 / SiO 2 is less than or equal to 0.1.
[0014] ZnO in glass can increase the chemical stability of glass and reduce the high-temperature viscosity of glass. 2The cooperation of these elements can suppress the volatilization of coloring materials during the melting stage, while promoting the structural change of coloring materials and improving the cut-off performance of glass. If the ZnO content is less than 5%, the cut-off performance of glass does not meet the requirements, and the chemical stability of glass is reduced. Therefore, the lower limit of the ZnO content is 5%, preferably 7%, and more preferably 9%. If the ZnO content exceeds 35%, the glass is prone to devitrification, especially during the molding and annealing stages, and the near-infrared transmittance of glass is significantly reduced. Therefore, the upper limit of the ZnO content is 35%, preferably 30%, and more preferably 25%.
[0015] In some implementations of the present invention, ZnO / SiO 2 If the value is less than 0.07, the chemical stability of the glass does not meet the design requirements, and the cut-off ability of the glass is reduced. 2 If the value is 0.95 or more, non-colored substances in the glass are likely to be devitrified, and the near-infrared transmittance, particularly in the range of 800 to 1000 nm, tends to decrease rapidly. 2 The value of is 0.07 to 0.95, more preferably 0.10 to 0.75, and further preferably 0.15 to 0.60. In this case, the threshold value for the generation of glass coloring substances can be lowered, which contributes to the improvement of cutoff performance and near-infrared transmittance.
[0016] Li, which belongs to the alkali metal oxides contained in the glass of the present invention, 2 O, Na 2 OK 2O can reduce the high-temperature viscosity of glass and reduce bubbles and inclusions in glass. On the one hand, it can reduce the high-temperature viscosity, and on the other hand, it can increase the solubility of coloring substances and improve the cut-off performance of glass. In addition, alkali metal oxides can supply more free oxygen, which can realize better cut-off performance and at the same time improve the near-infrared transmittance of glass. However, when the content is less than 8%, the above effects are not significant, and on the other hand, the expansion coefficient of glass is lower than the design target, which does not match well with materials with high hardness and high expansion coefficient. When the content exceeds 35%, the glass is easily devitrified, the cut-off performance and near-infrared transmittance decrease, and the chemical stability also rapidly decreases. Therefore, the alkali metal oxide Li 2 O+Na 2 O+K 2 The total content of O is 8 to 35%, preferably 9 to 30%, and more preferably 10 to 22%.
[0017] Li 2 O has an excellent ability to reduce the high-temperature viscosity of glass, and is useful for improving the essential quality of glass. However, the present inventors have found that Li ions have a strong ability to aggregate in glass and inhibit the structural change of coloring substances, thereby reducing the cut-off performance of the glass. In particular, if the content exceeds 5%, the glass cannot obtain the desired cut-off performance. Therefore, Li 2 The content of O is preferably 5% or less, more preferably 3% or less, and even more preferably 2% or less. 2 It is more preferable that it does not contain O.
[0018] Na in glass 2 O can reduce the high-temperature viscosity of glass and lower the threshold for structural changes of coloring materials. At the same time, it can improve the near-infrared transmittance of glass, increase the thermal expansion coefficient of glass, and facilitate the bonding of the glass of the present invention with high-strength transparent materials. 2 If the O content is less than 5%, the near-infrared transmittance of the glass does not meet the design requirements, the cut-off performance of the glass is reduced, and the thermal expansion coefficient of the glass is lower than the design requirements.2 The lower limit of the O content is 5%, preferably 7%, and more preferably 8%. 2 If the O content exceeds 25%, the chemical stability of the glass decreases, the glass becomes more susceptible to devitrification, the threshold for structural changes of coloring substances increases, and the cut-off performance of the glass decreases. 2 The upper limit of the O content is 25%, preferably 22%, and more preferably 19%.
[0019] In this glass system, K 2 The role of O is Na 2 Similar to O, but its ability to enhance near infrared is less than that of Na 2 stronger than O; on the other hand, its ability to reduce the chemical stability of glass and its resistance to devitrification is 2 It is stronger than O. Therefore, K 2 The O content is limited to 1 to 10%, preferably 2 to 8%, and more preferably 3 to 7%, from the viewpoint of optimizing the chemical stability, devitrification resistance, and cutoff performance of the glass.
[0020] Al in glass 2 O 3 Al can improve the chemical stability of glass, but it also causes a decrease in the cut-off performance of glass. If its content exceeds 5%, the cut-off performance of glass will not meet the design requirements. 2 O 3 The content of Al is 5% or less, preferably 3% or less. If there is a surplus in the chemical stability of the glass, Al 2 O 3 The content is more preferably 1% or less.
[0021] MgO improves the chemical stability of glass. However, if the content exceeds 5%, the devitrification resistance of glass decreases, the cutoff ability of glass decreases, and the near-infrared transmittance also decreases. Therefore, the content of MgO is limited to 5% or less, preferably 3% or less, and more preferably 2% or less.
[0022] CaO improves the stability and devitrification resistance of glass and reduces the high-temperature viscosity. If its content exceeds 5%, it inhibits the structure formation of coloring substances and reduces the cut-off performance of glass. Therefore, the CaO content is limited to 5% or less, preferably 3% or less, and more preferably 2% or less.
[0023] The appropriate amount of BaO and SrO in glass can improve the chemical stability of glass, increase the hardness of glass, and improve the near-infrared transmittance of glass. However, if the content exceeds 10%, the fixing ability of the coloring material in glass may decrease, and the cut-off ability may decrease. Therefore, the content of BaO and SrO is limited to 10% or less, preferably 5% or less, and more preferably 2% or less, respectively.
[0024] F in glass increases the melting property of glass, suppresses the volatilization of coloring substances during the supply stage, and improves the cut-off performance of glass. However, if the content exceeds 5%, the high-temperature viscosity of glass drops sharply and coloring substances volatilize excessively. Therefore, from the viewpoint of environmental protection, the F content is 5% or less, preferably 3% or less, more preferably 1% or less, and even more preferably 0%.
[0025] Since S can form coloring substances with Sb, Ag, Ce, Sn, Te, V, Fe, etc. in the glass of the present invention, the glass has a cutoff absorption in the band before 500 to 720 nm. If the S content exceeds 8%, the glass is easily devitrified and the near-infrared transmittance drops sharply. If the S content is less than 0.2%, the cutoff performance of the glass does not satisfy the design requirements. Therefore, the S content is limited to 0.2 to 8%, preferably 0.5 to 7%, and more preferably 1 to 6%. The S content in the present invention is the content of sulfur that is completely converted to elemental sulfur among all sulfur-containing substances in the glass. In the present invention, S can be introduced by elemental sulfur and / or a sulfur-containing compound.
[0026] Since Se can form coloring substances with Sb, Ag, Ce, Sn, Te, V, Fe, etc. in the glass of the present invention, the glass generates cutoff absorption in the band before 650 to 1200 nm, and can be made into a glass with better cutoff performance than simple S or sulfides. If the content of Se exceeds 5%, the glass is easily devitrified and the near-infrared transmittance drops sharply. Therefore, when the cutoff performance satisfies the design requirements, the content of Se in the present glass system is 5% or less, preferably 4% or less, more preferably 3% or less, and even more preferably 0%. The content of Se in the present invention is the content of selenium that is completely converted to elemental selenium among all selenium-containing substances in the glass. In the present invention, Se can be introduced by elemental selenium and / or a selenium-containing compound.
[0027] Through extensive experimental research, the present invention has found that in some implementations, when the Se / S value exceeds 1.5, the transmittance of the glass at 800-1000 nm does not meet the design requirements. Therefore, the Se / S value is preferably 1.5 or less, more preferably 1.3 or less, even more preferably 1.0 or less, and even more preferably 0.5 or less.
[0028] At least one of the components such as Sb, Ag, Ce, Sn, Te, V, and Fe in the glass of the present invention can form a colored compound with S and / or Se. If the total content of Sb+Ag+Ce+Sn+Te+V+Fe exceeds 10%, the glass is prone to devitrification, and the near-infrared transmittance drops sharply. If the total content of Sb+Ag+Ce+Sn+Te+V+Fe is less than 0.5%, colored substances are unlikely to be generated in the glass, and the cutoff performance as designed cannot be obtained. Therefore, the content of Sb+Ag+Ce+Sn+Te+V+Fe is 0.5 to 10%, preferably 0.8 to 9%, and more preferably 0.9 to 8%. The content of Sb+Ag+Ce+Sn+Te+V+Fe in the present invention means the total content of Sb in the Sb-containing material, Ag in the Ag-containing material, Ce in the Ce-containing material, Sn in the Sn-containing material, Te in the Te-containing material, V in the V-containing material, and Fe completely converted to elements in the Fe-containing material in the glass. Sb, Ag, Ce, Sn, Te, V, and Fe may be introduced by oxides, and / or sulfides, and / or selenides, and / or fluorides, and / or simple substances, and / or compound salts, and / or hydroxides, etc. In some implementations of the present invention, it is preferable to not include Sn and / or Te.
[0029] In some implementations of the present invention, when (Sb+Ag+Ce+Sn+Te+V+Fe) / (S+Se) is less than 0.1, the near-infrared transmittance of the glass is significantly reduced, and when (Sb+Ag+Ce+Sn+Te+V+Fe) / (S+Se) is more than 25.0, the cutoff performance of the glass is significantly reduced, and the devitrification resistance of the glass is also rapidly reduced. Therefore, the value of (Sb+Ag+Ce+Sn+Te+V+Fe) / (S+Se) is preferably 0.1 to 25.0, more preferably 0.2 to 15.0, even more preferably 0.5 to 8.0, and even more preferably 1.0 to 5.0.
[0030] In some implementations of the present invention, there is a synergistic effect when Sb, Ag, Ce, Sn, Te, V, and Fe form coloring substances with anions in glass; when the value of (Ag+Ce+Sn+Te+V+Fe) / Sb is greater than 3.0, the near-infrared transmittance of the glass is significantly reduced. Therefore, it is preferable that the value of (Ag+Ce+Sn+Te+V+Fe) / Sb is 3.0 or less, more preferably 2.0 or less, even more preferably 1.0 or less, and even more preferably 0.8 or less.
[0031] In some implementations of the present invention, CuO, TiO 2 , and P 2 O 5 It is possible to further include one or more of CuO, TiO 2 , P 2 O 5 The total content of CuO+TiO 2 +P 2 O 5 ) exceeds 0.5%, the glass is particularly susceptible to devitrification, and the structure of the coloring material changes negatively, making it easy for the near infrared transmittance to decrease sharply. 2 +P 2 O 5 The content of CuO+TiO is less than 0.5%. 2 +P 2 O 5 If the content is less than 0.0001%, the coloring substance can only be formed in the impurity defects in the glass, which causes problems such as poor cutoff performance of the glass and poor coloring uniformity of the glass. Therefore, it is preferable to use CuO+TiO 2 +P 2 O 5 The content of CuO and TiO in the present invention is 0.0001 to 0.5%, more preferably 0.0001 to 0.4%, and further preferably 0.0001 to 0.3%. 2 and P 2 O 5 The content of CuO, TiO 2 and P 2 O 5 It is not included in the 100wt% which consists of the content of all other components.
[0032] <Unnecessary ingredients> Due to environmental considerations, the glass of the present invention does not contain Cd, As or Pb. Here, "free" and "0%" mean that compounds, molecules, elements, etc. are not intentionally added as raw materials for the glass of the present invention; however, if there are small or trace amounts of specific impurities or components that are not intentionally added as raw materials and / or equipment for the production of glass in the final glass, this situation is also included in the scope of protection of the patent of the present invention.
[0033] The characteristics of the environmentally friendly glass material of the present invention will be described below.
[0034] <Cut-off performance> Using a spectrometer according to the method of GB / T7962.12-2010, the transmittance curve of 3mm glass sample at 300nm~2000nm is tested, and the transmittance of 5% is the cut-off wavelength. In the present invention, the higher the cut-off wavelength value of the glass, the better the cut-off performance, and the lower the cut-off wavelength value, the worse the cut-off performance.
[0035] In some implementations of the present invention, the cutoff wavelength of the environmentally friendly glass material is 550 nm or more, preferably 600 nm or more, more preferably 650 nm or more, even more preferably 680 nm or more, and even more preferably 700 nm or more.
[0036] <Near infrared transmittance> The transmittance curve of the glass in the range of 300nm to 2000nm of a 3mm glass sample is tested using a spectrometer according to the method of GB / T7962.12-2010, and the near-infrared transmittance in the present invention refers to the transmittance value in the range of 800nm to 2000nm. Note that, the near-infrared transmittance in the present invention refers to the lowest transmittance in the corresponding wavelength band range.
[0037] In some implementations of the present invention, the environmentally friendly glass material of the present invention has one or more of the following transmittances:
[0038] 1) The transmittance from 800 to 850 nm is 75% or more, preferably the transmittance from 800 to 850 nm is 77% or more, and more preferably the transmittance from 800 to 850 nm is 80% or more.
[0039] 2) The transmittance from 850 to 900 nm is 80% or more, preferably the transmittance from 850 to 900 nm is 82% or more, and more preferably the transmittance from 850 to 900 nm is 83% or more.
[0040] 3) The transmittance from 900 to 1000 nm is 83% or more, preferably the transmittance from 900 to 1000 nm is 84% or more, and more preferably the transmittance from 900 to 1000 nm is 85% or more.
[0041] 4) The transmittance from 1000 to 2000 nm is 85% or more, preferably the transmittance from 1000 to 2000 nm is 86% or more, and more preferably the transmittance from 1000 to 2000 nm is 87% or more.
[0042] <Acid resistance stability> Acid resistance of glass materials (D A ) (powder method) is tested in accordance with the method specified in GB / T 17129. Here, acid resistance is sometimes called acid resistance or acid stability.
[0043] In some implementations of the present invention, the acid stability (D A ) is class 3 or higher, preferably class 2 or higher, and more preferably class 1.
[0044] <Water resistance stability> Water resistance stability of glass materials (D W ) (powder method) is tested in accordance with the method specified in GB / T 17129. Here, water resistance is sometimes called water resistance or water stability.
[0045] In some implementations of the present invention, the water resistance stability (D W) is class 3 or higher, preferably class 2 or higher, and more preferably class 1.
[0046] <Thermal expansion coefficient> The thermal expansion coefficient in the present invention refers to the average thermal expansion coefficient of glass at 20 to 300 ° C., and α 20-300℃ and is tested according to the method specified in GB / T7962.16-2010.
[0047] In some implementations of the present invention, the average thermal expansion coefficient (α 20-300℃ ) is 80 x 10 -7 / K or more, preferably 85×10 -7 / K or more, preferably 90×10 -7 / K or more, and more preferably 95×10 -7 / K or higher.
[0048] [Manufacturing method] The method for producing the environmentally friendly glass material of the present invention includes the following steps: 1) Mix all the raw materials according to the component ratio of the environmentally friendly glass material, put the homogeneously mixed raw materials into a melting furnace, and melt them at 1300~1500℃ to form molten glass; 2) Stirring and homogenizing the molten glass; 3) Pouring or leaking the molten glass into a mold to form it; 4) The glass formed in step 3) is held at 470 to 600°C for 10 to 60 hours to develop color, or the glass formed in step 3) is further processed into a glass preform or a glass member, and then held at 470 to 600°C for 10 to 60 hours to develop color.
[0049] Furthermore, the raw materials for the above-mentioned environmentally friendly glass material may be composite salts (carbonates, sulfates, nitrates, etc.), and / or hydroxides, and / or oxides, and / or sulfides, and / or selenides, and / or fluorides, and / or simple substances.
[0050] [Glass preforms and glass components] A glass preform can be produced from the environmentally friendly glass material by compression molding means such as grinding or reheat forming, precision stamping, etc. That is, a glass preform can be produced by polishing and other mechanical processing of the environmentally friendly glass material, a glass preform can be produced by producing a preform for compression molding from the environmentally friendly glass material, reheat forming this preform and polishing it, or a glass preform can be produced by precision stamping the preform produced by polishing.
[0051] The means for producing the glass preform is not limited to the above means.
[0052] The glass preform and glass member of the present invention are both formed from the above-mentioned environmentally friendly glass material of the present invention. The glass preform of the present invention has the excellent properties of the environmentally friendly glass material, and the glass member of the present invention has the excellent properties of the environmentally friendly glass material, and can provide various valuable glass members such as filters, lenses, and prisms.
[0053] [device] The environmentally friendly glass material of the present invention and glass members formed therefrom can be used in the manufacture of optical filters, photographic devices, camera equipment, display equipment, surveillance equipment, electronic equipment, intelligent equipment, and the like.
[0054] Embodiment In order to further clearly describe and illustrate the technical solutions of the present invention, the following non-limiting embodiments 1 to 22 are provided.
[0055] In this embodiment, the manufacturing method of the environmentally friendly glass material described above is used to obtain an environmentally friendly glass material having the components shown in Tables 1 to 3. In addition, the properties of each glass were measured by the test methods described in the present invention, and the results are shown in Tables 1 to 3. [Table 1]
Table 2
Table 3
Claims
1. SiO 2 An environmentally friendly glass material containing the components of SiO, ZnO, alkali metal oxides, and S, and not containing Cd, the components being expressed in weight percent: 2 35-80%, ZnO 5-35%, Na 2 O 5-25%, K 2 An environmentally friendly glass material which, when it contains 1-10% O, 0.2-8% S, and 2-4.2% Sb, has a cutoff wavelength of 550 nm or more, a transmittance of 75% or more at 800-850 nm, a transmittance of 80% or more at 850-900 nm, a transmittance of 83% or more at 900-1000 nm, and a transmittance of 85% or more at 1000-2000 nm, when it has a thickness of 3 mm.
2. If the environmentally friendly glass material has a thickness of 3 mm, 1) Cutoff wavelength is 650 nm or more, 2) Transmittance of 77% or more at 800-850 nm, 3) Transmittance of 82% or more at 850 to 900 nm 4) Transmittance of 84% or more at 900 to 1000 nm 5) Transmittance of 86% or more from 1000 to 2000 nm 2. The environmentally friendly glass material according to claim 1, which satisfies one or more of the above five conditions.
3. If the environmentally friendly glass material has a thickness of 3 mm, 1) Cutoff wavelength is 700 nm or more, 2) Transmittance of 800 to 850 nm is 80% or more. 3) Transmittance of 83% or more at 850-900 nm 4) Transmittance of 85% or more at 900 to 1000 nm 5) Transmittance of 87% or more from 1000 to 2000 nm 2. The environmentally friendly glass material according to claim 1, which satisfies one or more of the above five conditions.
4. Its components are expressed in weight percent: Sb+Ag+Ce+Sn+Te+V+Fe in the range of 0.5 to 10%; and / or Li 2 O 0-5%; and / or B 2 O 3 and / or Al 2 O 3 and / or 0-5% MgO; and / or 0-5% CaO; and / or 0-10% SrO; and / or 0-10% BaO; and / or 0-5% Se; and / or 0-5% F.
5. Its components, expressed in weight percent, are: SiO 2 and / or ZnO in an amount of 7 to 30%; and / or Na 2 O 7-22%; and / or K 2 O 2-8%; and / or Li 2 O is 0 to 3%; and / or S is 0.5 to 7%; and / or Sb+Ag+Ce+Sn+Te+V+Fe is 0.8 to 9%; and / or B 2 O 3 and / or Al 2 O 3 and / or 0-3% MgO; and / or 0-3% CaO; and / or 0-5% SrO; and / or 0-5% BaO; and / or 0-4% Se; and / or 0-3% F.
6. Its components, expressed in weight percent, are: SiO 2 and / or ZnO in an amount of 9 to 25%; and / or Na 2 O 8-19%; and / or K 2 O 3-7%; and / or S 1-6%; and / or Sb+Ag+Ce+Sn+Te+V+Fe 0.9-8%; and / or Se 0-3%; and / or Li 2 O 0-2%; and / or B 2 O 3 and / or Al 2 O 3 and / or 0-2% MgO; and / or 0-2% CaO; and / or 0-2% SrO; and / or 0-2% BaO; and / or 0-1% F.
7. Its components expressed in weight percent are: CuO + TiO 2 +P 2 O 5 5. The environmentally friendly glass material according to claim 1, comprising 0 to 0.5% of
8. Its components are expressed in weight percent: CuO + TiO 2 +P 2 O 5 5. The environmentally friendly glass material according to claim 1, containing 0.0001 to 0.3% of
9. The components are expressed in weight percent, 1) B 2 O 3 / SiO 2 is 0.23 or less, 2) ZnO / SiO 2 is 0.07 to 0.95, 3) Se / S is 1.5 or less, 4) (Sb+Ag+Ce+Sn+Te+V+Fe) / (Se+S) is 0.1 to 25.0, 5) (Ag+Ce+Sn+Te+V+Fe) / Sb is 3.0 or less, 6) Li 2 O + Na 2 O+K 2 5. The environmentally friendly glass material according to claim 1, wherein O is 8 to 35%.
10. The components are expressed in weight percent, 1) B 2 O 3 / SiO 2 is 0.15 or less, 2) ZnO / SiO 2 is 0.10 to 0.75, 3) Se / S is 1.0 or less, 4) (Sb+Ag+Ce+Sn+Te+V+Fe) / (Se+S) is 0.5 to 8.0, 5) (Ag+Ce+Sn+Te+V+Fe) / Sb is 2.0 or less, 6) Li 2 O + Na 2O+K 2 O 9%–30% 5. An environmentally friendly glass material according to claim 1, which satisfies one or more of the six conditions above.
11. The components are expressed in weight percent, 1) B 2 O 3 / SiO 2 is less than 0.1, 2) ZnO / SiO 2 is 0.15 to 0.60, 3) Se / S is 0.5 or less, 4) (Sb+Ag+Ce+Sn+Te+V+Fe) / (Se+S) is 1.0 to 5.0, 5) (Ag+Ce+Sn+Te+V+Fe) / Sb is 0.8 or less, 6) Li 2 O + Na 2 O+K 2 O 10%–22% 5. An environmentally friendly glass material according to claim 1, which satisfies one or more of the six conditions above.
12. The environmentally friendly glass material has an acid resistance stability of Class 1; and / or a water resistance stability of Class 1; and / or a thermal expansion coefficient of 95×10 -7 5. The environmentally friendly glass material according to claim 1, wherein the glass has a molecular weight of 1.0 to 1.2 kg / K or more.
13. A glass preform using the environmentally friendly glass material according to any one of claims 1 to 12.
14. A glass member using the environmentally friendly glass material according to any one of claims 1 to 12 or the glass preform according to claim 13.
15. A device comprising the environmentally friendly glass material according to any one of claims 1 to 12 and / or the glass member according to claim 14.
16. A method for producing an environmentally friendly glass material according to any one of claims 1 to 12, comprising the steps of: 1) Mix all the raw materials according to the component ratio of the environmentally friendly glass material, put the homogeneously mixed raw materials into a melting furnace, and melt them at 1300-1500℃ to form molten glass; 2) Stirring and homogenizing the molten glass; 3) Pouring or leaking the molten glass into a mold to form it; 4) The glass formed in step 3) is kept at 470 to 600°C for 10 to 60 hours to develop color, or the glass formed in step 3) is further processed into a glass preform or glass member, and then kept at 470 to 600°C for 10 to 60 hours to develop color. A manufacturing method for environmentally friendly glass materials.
17. 17. The method for producing an environmentally friendly glass material according to claim 16, wherein compound salts, and / or hydroxides, and / or oxides, and / or sulfides, and / or selenides, and / or fluorides, and / or simple substances are used as raw materials for the environmentally friendly glass material.
Citation Information
Patent Citations
JP1975040609A
Optical colored glass, method of using the optical colored glass, and optical edge filter
JP2003119049A
Colored optical glass
JP2003160357A
Manufacturing process of microparticle dispersion glass and ultraviolet cut filter
JP2005206434A
